Medical Tourism, Radical Democracy and Its Discontents: The Case of Indonesia - Pasopati, Rommel Utungga; Ramadhani, Riska Dewi; Wijaya, Kusuma (UIN Sunan Ampel Surabaya, 2024)
This article underlines tensions between medical tourism and radical democracy in Indonesian sense. Medical tourism tends to prioritize those who have money to gain more options, yet change the ideas of medical aspects into such trivial recreations. Meanwhile, radical democracy works to realize such welfare states in which all people could reach better options in life. Radical democracy, as indicated by Ernesto Laclau and Chantal Mouffe, is analyzed through genealogy of hegemony as discourses that are used to be owned by several people are distributed to every person’s needs. Through qualitative method and explorative approach, the analysis of this paper emphasizes on how radical democracy promotes undeveloped people to have better access to basic needs but medical tourism still asks answers from capitalism itself. The discourses will only remain as dialogues while the applications of being ideational have shifted into matters of being recreational. Intertwinements of medical aspects and tourism indeed focuses on those who travel and stay, but will slowly eradicate the truth of the needs of those who need better medical assistances. In conclusion, while radical democracy would like to erode hegemony, medical tourism worsens the situation by pushing more trickle-down effects than fairness and equality before everyone.